Code-Switching in Egyptian Rap Songs - Koriem, Rehab (AUC Knowledge Fountain, 2026)
This thesis seeks to examine code-switching in contemporary Egyptian rap songs, focusing on the linguistic and cultural roles of code-switching among Egyptian Arabic, English, and other languages. Analyzing some well-known Egyptian rap artists, the study highlights code-switching as both a stylistic device and a sociocultural practice reflecting globalization, youth culture, and urban identity in Egypt. It investigates two main aspects: the linguistic features of code-switching in rap and its role in identity negotiation and linguistic-cultural hybridity. Employing a qualitative discourse-analytic approach linked to sociolinguistics and cultural studies, guided by Myers-Scotton’s Markedness Model, the analysis identifies language alternation patterns and their communicative functions. The findings reveal that code-switching serves multiple purposes, including the expression of modernity, social belonging, authenticity, resistance, creativity, and affiliation with global culture. English and other language insertions shape a cosmopolitan youth identity, while Egyptian Arabic maintains local authenticity. Ultimately, the thesis argues that code-switching is not merely a linguistic feature but a cultural strategy for rappers to express hybridity, redefine modern Egyptian youth identities, and connect with international rap norms, while preserving local linguistic and cultural characteristics.